Histopathological profile of patients diagnosed with malignant tumors assisted in a hospital of reference of Agreste Pernambucano - Ana Kátia S. Teixeira; Juliana Lúcia A. Vasconcelos (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT Cancer is considered a public health problem and is commonly known because of its high mortality rate worldwide. The histopathological evaluation is a fundamental requirement to determine the nature of the lesion, thus it is considered the gold standard examination for diagnosis of neoplasia. The present study aims to evaluate the histopathological profile of patients with malignant tumors diagnosed at a reference hospital in the Agreste Pernambucano. A cross-sectional, descriptive study of a quantitative documentary survey was conducted using the database of the clinical analysis laboratory of the referred Hospital in the field of pathology in the year 2016. A total of 74 cases were selected, and the male gender was the most affected. The age group of patients with the highest prevalence was between 50 and 70 years of age. Clinical characteristics: The most prevalent anatomical location with tumors was both the colon/rectum (30%) and skin (30%). The most common histological type was adenocarcinoma (47.2%). The pathological profile of cancer patients in the region studied were characterized, which served as a database for future epidemiological studies and as a subsidy for the implementation of preventive public policies for the population of this region.